MENGEMBANGKAN MOTIVASI BELAJAR MELALUI LOCUS Of CONTROL dan SELF ESTEEM - Fadila, Fadila (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2016)
In this paper, the research aims to find the learning motivation of someone by developingsefl-award and self-control locus that known âSelf esteemâ and âLocus of controlâ. It consists of two parts, namely self esteemdan locus of control. Self esteem uses ones knowledge abouthimself and judges himself.It can classified into very high, high, medium, low and very low.While the locus of control is howself control of someone to events happened. There are two forms of characteristics of individuals based on the tendency of the locus control. Both are internal and external forms.Someone who has an internal locus of control,the factor of ability and effort seems dominant. Therefore, if an individual with experience of failure of internal control locusof they will blame himself for the lack of effort made. Similarly, the success, they will feel proud of the results of his efforts.Individuals who have characteristics with High self-estream can be described that the individualsare active and able to express themselves well.They excel academically and succeed in social relations. they can take criticism well, believe in the perception and himself,have belief of himself not only by his imagination. Because they have the ability, social skills, and the quality of high self-esteem, then they are not susceptible to the judgment of others regarding their nature and personality, either positive or negative.it is easy for them to adjust to the new environment.They have low levels of anxiety and insecurity. They have the power for balanced surviving.